Peran Amal Madani Indonesia (AMI) dalam Pemberdayaan Ekonomi Umat Melalui Zakat di Kota Cimahi - Rini Rismayanti; Desy Dahliani; Triana Apriani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Amal Madani Indonesia (AMI) is a zakat philanthropic institution based in Cimahi, West Java, with a vision to empower communities through professional, transparent, and accountable management of zakat, infaq, and alms (ZIS) funds. As a zakat institution, AMI focuses not only on the collection and distribution of funds but also emphasizes the importance of good governance so that the collected funds can have a real impact on improving community welfare. This study aims to analyze AMI's contribution to improving community economic empowerment, evaluate the efficiency of zakat distribution, and examine the practice of Islamic philanthropic governance in the Cimahi region. The research method used is a descriptive qualitative approach with data collection techniques through field observations, documentation studies, and in-depth interviews with administrators and beneficiaries. The results show that AMI has a significant role in encouraging the socio-economic development of the surrounding community. The programs implemented are not only oriented towards distributing consumer assistance, but also focus on sustainable empowerment, for example through entrepreneurship training, mentoring micro, small, and medium enterprises (MSMEs), providing access to capital, and providing educational scholarships for children from underprivileged families. This strategy demonstrates that AMI is striving to shift the paradigm of zakat from merely a means of distributing welfare to an instrument for the economic development of the community. However, research also found several obstacles faced, including the program's distribution reach which is still limited to certain areas, limited human resources in managing empowerment programs, and low levels of zakat literacy among the community. The low understanding of some communities regarding the obligation of zakat has an impact on the potential for zakat collection that is not optimal. Therefore, efforts are needed to improve zakat education, optimize digital technology in collection and distribution, and strengthen collaboration with various parties, both government and the private sector.